INSTALLATION OF SIGNS TO MARK THE BOUNDARIES BETWEEN HAMLETS IN NYALABU LAOK VILLAGE, PAMEKASAN - Risca Dwiaryanti; Fitriyatun Hasanah (PT Altin Riset Publishing, 2026)
The community service project carried out by students from the PKN program at IAI Al-Khairat Pamekasan lasted for 30 days. The objective of this program was to address a common issue faced by both local residents and newcomers—confusion regarding the names and boundaries of hamlets. The boundary signs installed between hamlets and villages have been very helpful in making it easier for the community to identify the names of these hamlets. To achieve the intended goals of the program to install boundary signs between hamlets and villages in Nyalabu Laok Village, the work was carried out through hands-on practice by PKN students, village officials, and the local community. The installation of these signs took approximately two weeks. The result was that the students and local residents were very satisfied with the installation of these village boundary signs because they help residents recognize the names and boundaries of hamlets in Nyalabu Laok Village.